2017
DOI: 10.1111/jth.13658
|View full text |Cite
|
Sign up to set email alerts
|

A first‐in‐human study of DS‐1040, an inhibitor of the activated form of thrombin‐activatable fibrinolysis inhibitor, in healthy subjects

Abstract: Background Current treatments for acute ischemic stroke and venous thromboembolism, such as recombinant tissue-type plasminogen activator and thrombectomy, are limited by a narrow time window and the risk of bleeding. DS-1040 is a novel low molecular weight compound that inhibits the activated form of thrombin-activatable fibrinolysis inhibitor (TAFIa), and was developed as a fibrinolysis enhancer for the treatment of thromboembolic diseases. Objectives This first-in-human, randomized, placebo-controlled, thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 34 publications
9
49
0
Order By: Relevance
“…Multiple daily dosing of DS‐1040 did not lead to a significant accumulation in exposure; steady state was attained by day 7 with minimal accumulation (mean accumulation ratio 1.15‐1.25) compared with predose plasma DS‐1040 concentrations on day 10. The t ½ values observed in this study for the oral formulation of DS‐1040 were in line with previously reported results for DS‐1040 administered via IV . This suggests that the oral formulation of DS‐1040 will be suitable for use in patients.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Multiple daily dosing of DS‐1040 did not lead to a significant accumulation in exposure; steady state was attained by day 7 with minimal accumulation (mean accumulation ratio 1.15‐1.25) compared with predose plasma DS‐1040 concentrations on day 10. The t ½ values observed in this study for the oral formulation of DS‐1040 were in line with previously reported results for DS‐1040 administered via IV . This suggests that the oral formulation of DS‐1040 will be suitable for use in patients.…”
Section: Discussionsupporting
confidence: 92%
“…Approximately 10% of the administered dose was recovered as intact parent drug in urine. This is lower than the percentage of parent drug recovered in urine after IV administration (44%‐93%) . Multiple daily dosing of DS‐1040 did not lead to a significant accumulation in exposure; steady state was attained by day 7 with minimal accumulation (mean accumulation ratio 1.15‐1.25) compared with predose plasma DS‐1040 concentrations on day 10.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations